Humaniversity: humanising the university - Razak, Dzulkifli Abd (2011)
N my annual address for 2011 to the university community last week, I spoke about Humaniversity: Transformation to Humanise the University. This is perhaps the culmination of 11 years of provoking it to look for new vistas to give meaning to universities, and higher education, in particular. Over the last decade, the threat against the university as an institution in its own right has never been more intense. Drawing an analogy between the university and a frog in simmering water, universities have, by and large, accommodated the slow boil so far.